Advances on Thermally Conductive Epoxy‐Based Composites as Electronic Packaging Underfill Materials—A Review (Adv. Mater. 52/2022). Issue 52 (28th December 2022) - Wen, Yingfeng; Chen, Chao; Ye, Yunsheng; Xue, Zhigang; Liu, Hongyuan; Zhou, Xingping; Zhang, Yun; Li, Dequn; Xie, Xiaolin; Mai, Yiu‐Wing
Abstract : Capillary Underfill Materials Underfill materials with high thermal conductivity play crucial roles in ensuring the reliability and performance of microelectronic devices with ever‐increasing power density. In article number 2201023, Xiaolin Xie, Yiu‐Wing Mai, and co‐workers review the state‐of‐the‐art advances on capillary underfill materials and give future perspectives for designing high‐performance underfill materials with novel microstructures.